A model of quiescent tumour microregions for evaluating multicellular resistance to chemotherapeutic drugs. - Mellor, H; Ferguson, D; Callaghan, R (2005)
The quiescent cell population of tumours poses a barrier to the success of many cancer therapies. Most chemotherapeutic drugs target proliferating cells, but the growth fraction of many tumours is low. Based on the multicellular tumour spheroid model, a system was developed using human colon adenocarcinoma (DLD-1) cells to mimic the microenvironment of quiescent microregions of solid tumours. The quiescent tumour spheroids (TS(Q)) showed decreased expression of the proliferation marker Ki-67 and increased expression of the quiescence marker p27(kip1) compared to proliferating spheroids (TS(P)). The quiescent status of the TS(Q) was confirmed by long-term growth assessment. The quiescence was completely reversible demonstrating that the TS(Q) retained the ability to proliferate and morphological assessment by light microscopy confirmed the absence of significant apoptosis. When the efficacy of widely used chemotherapeutic drugs was determined, vinblastine, doxorubicin, cisplatin and 5-fluorouracil (5-FU) all produced significant cell death in the TS(P). However, while still effective, the potencies of doxorubicin and cisplatin were significantly reduced in TS(Q). In contrast, 5-FU and vinblastine did not produce cell death in the TS(Q). In summary, TS(Q) show considerable resistance to a panel of established chemotherapeutic agents and represent a useful model for evaluating the efficacy of drugs and other cancer therapies in quiescent tumours.